2016
DOI: 10.1016/j.atherosclerosis.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The novel selective PPARα modulator (SPPARMα) pemafibrate improves dyslipidemia, enhances reverse cholesterol transport and decreases inflammation and atherosclerosis

Abstract: These results demonstrate that the novel selective PPARα modulator pemafibrate exerts beneficial effects on lipid metabolism, RCT and inflammation resulting in anti-atherogenic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 40 publications
3
98
2
Order By: Relevance
“…Considering the relative concentrations of these drugs, results show that K‐877 activates the PPARα transcription activity more effectively than the other agents. To determine the effects of K‐877 on fibroblast growth factor 21 ( Fgf21 ) expression, a typical target gene of PPARα, in vitro , mouse AML12.2 hepatoma cells were incubated with the PPARα agonists, Feno (50 μmol/L) or K‐877 (5 and 50 μmol/L) for 48 h based on a previous report. Both doses of K‐877 significantly increased Fgf21 expression, but the increase in expression by Feno was slight (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the relative concentrations of these drugs, results show that K‐877 activates the PPARα transcription activity more effectively than the other agents. To determine the effects of K‐877 on fibroblast growth factor 21 ( Fgf21 ) expression, a typical target gene of PPARα, in vitro , mouse AML12.2 hepatoma cells were incubated with the PPARα agonists, Feno (50 μmol/L) or K‐877 (5 and 50 μmol/L) for 48 h based on a previous report. Both doses of K‐877 significantly increased Fgf21 expression, but the increase in expression by Feno was slight (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…K-877 suppresses MCD-induced liver injury in normal mice, but not in Ppara -/mice To compare the effects of PPARa agonists on the progression of NAFLD, WT and Ppara -/mice were fed an MCD diet containing 0.1% Feno or 0.00025% K-877 for 4 weeks, and their optimum doses were determined according to previously reported methods 7,12 . This diet has been used extensively to produce diet-induced animal models of NASH that show similar histology to that of human NASH 1 .…”
Section: K-877 Decreased Plasma Lipid Levels In Wt Micementioning
confidence: 99%
“…There are no published data on pemafibrate directly inducing apoA-I gene expression; however, apoA-I gene expression has been shown to be induced by PPARa agonists. 21 Pemafibrate increased plasma apoA-I levels in human apoA-I transgenic mice, where pemafibrate induced greater apoA-I level increase than fenofibrate with less increase of liver weight, 28 indicating its favorable balance of the efficacy and safety with regard to the liver compared to fenofibrate. In fact, pemafibrate did not increase but rather significantly decreased mean levels of alanine aminotransferase and g-glutamyl transpeptidase, whereas fenofibrate increased these levels.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27] In vivo and in vitro studies found that pemafibrate enhanced CEC, RCT, and TRL catabolism, suppressed TRL production, and exerted anti-inflammatory and antiatherosclerotic effects. 28 Therefore, the present study aimed to investigate the effects of pemafibrate on CEC and postprandial hyperlipidemia in patients with atherogenic dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…Pemafibrate (K-877) is a novel member of the selective PPARα modulator (SPPARMα) family [137] that was designed to have a higher PPARα agonistic activity and selectivity than existing PPARα agonists (such as fibrates) [138]. Pemafibrate exhibits protective antiatherogenic properties in mice by its TG and remnant lipoprotein-lowering effects, its beneficial effects on HDL metabolism and RCT and its anti-inflammatory activity in macrophages and the arterial wall, resulting in reduced atherosclerosis burden [139]. In phase III clinical trials, compared to fenofibrate, pemafibrate has greater PPARα activation in vitro and lower effects on TGs than fenofibrate.…”
Section: Ppar Ligand Therapeutics In Lipid Metabolism Disordermentioning
confidence: 99%